Views of Piano Teachers Regarding the Piano Education Process in Amateur Music Education Institutions - Ezgi KARAN; Hamit YOKUS (Anı Publishing, 2022)
This research aims to evaluate the piano education process in private education institutions in Amateur Music Education that provide private music education in line with the opinions of piano teachers. The research study group consists of piano teachers working in the institutions affiliated to the Ministry of National Education in the province of Antalya, Muratpasa, in the Fall Semester of the 2020-2021 Academic Year. The research is a case study. The research data were obtained with the semi-structured interview form created by the researchers and analyzed descriptively. As a result of the research, it was found that piano teachers usually work with preschool and elementary school students, especially with beginners and middle school students. Some piano teachers work with students preparing for conservatories, art high schools and special examinations of pedagogical faculties. Research has shown that the most important expectations of piano lessons are primarily from parents. It has been determined that piano teachers generally adopt a "middle-do" position-based education approach, and they prefer the show-and-make method within the framework of teaching method. In addition to these, they used more than one method together instead of a single method in their education processes; in the selection of repertoire, they take into account the expectations and orientations of the students; It was determined that the majority of the teachers did not have sufficient knowledge about learning strategies, they did not use learning strategies consciously in the education process, and they rewarded the students more in order to increase their motivation.